Comparison of Diagnostic Reliability of Ultrasound and Magnetic Resonance Cholangiopancreatography in Patients with Obstructive jaundice (Birat Journal of Health Sciences, 2025)
Introduction : Accurate identification of the underlying cause of obstructive jaundice is essential for selecting the most appropriate management strategy. Imaging plays a crucial role in the diagnosis, with ultrasound often used as an initial investigation and magnetic resonance cholangiopancreatography as a non-invasive alternative to invasive cholangiography. Objectives :To compare the diagnostic performance of USG and MRCP in determining the etiology of obstructive jaundice, using the final clinical, surgical, or endoscopic diagnosis as the reference standard.Methodology :This prospective cross-sectional study included 52 patients presenting with clinical and biochemical evidence of obstructive jaundice. All patients underwent both USG and MRCP. Imaging findings were correlated with the final diagnosis obtained from surgical, endoscopic, or clinical follow-up data. Sensitivity, specificity, accuracy, positive predictive value (PPV), negative predictive value (NPV), and kappa (κ) agreement were calculated for each modality.Results :The patients ranged in age from 20 to 80 years (mean = 53.7 ± 14.7 years), with a male-to-female ratio of 1.9:1. The most common cause of obstruction was choledocholithiasis (48.1%), followed by common bile duct stricture (13.5%) and cholangiocarcinoma (17.3%).USG demonstrated sensitivity of 66.7%, specificity of 94.6%, and accuracy of 86.5%, with a κ-value of 0.65 (substantial agreement). MRCP showed higher sensitivity (93.3%), specificity (97.3%), and accuracy (96.2%), with a κ-value of 0.91 (almost perfect agreement) when compared with the final diagnosis.Conclusion :MRCP provides superior diagnostic performance compared to USG in evaluating the cause of obstructive jaundice, particularly in identifying choledocholithiasis and malignant lesions. While USG remains a valuable initial screening modality, MRCP should be preferred for definitive diagnosis and treatment planning.